EU-ACP Economic Partnership Agreements : Empirical Evidence for Sub-Saharan Africa - Vollmer, Sebastian; Martínez-Zarzosoy, Inmaculada; Nowak-Lehmann D., Felicitas; Klan, Nils-Hendrik (Washington, DC: World Bank, 2012)
Since early 2008 there have been interim trade agreements between the EU and six regions of ACP countries in force which could be stepping stones towards full Economic Partnership Agreements between the EU and all ACP countries. This paper estimates the welfare effects of the interim agreements for nine African countries: Botswana, Cameroon, Cote d'Ivoire, Ghana, Kenya, Mozambique, Namibia, Tanzania, and Uganda. Results indicate that Botswana, Cameroon, Mozambique, and Namibia will significantly profit from the interim agreements, while the trade effects for Cote d'Ivoire, Ghana, Kenya, Tanzania, and Uganda are close to zero. Predicted results of the liberalization based on the interim agreement's reduction rates fall short of the potential of a full liberalization.